The Effectiveness of Tajik Lifestyle Modification on Successful Pregnancy in Women Candidates for Oocyte Donation with Ovarian Reserve Below 0.2: A Case Study - Tajiki, Flora (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: The present study aimed to determine the effectiveness of Tajik lifestyle modification on successful pregnancy in women candidates for oocyte donation with ovarian reserve below 0.2. Methods and Materials: This research was conducted as a single-case study. Ten patients diagnosed with reduced ovarian reserve and meeting the inclusion criteria were selected from among infertility treatment candidates in Tehran, who had not responded to conventional infertility treatments. Patients were chosen through online consultations and received daily counseling to assess and modify their lifestyle for 15 minutes per day until delivery, under the supervision of a midwifery specialist. The tools used in the study included structured clinical interviews, a demographic questionnaire, complete blood count (CBC) tests, hormonal tests (AMH, LH, FSH, DHEAS, TSH, Vitamin D3, and Estradiol), and sixth-day menstrual cycle ultrasound to examine antral follicle count, ovarian volume, and size. These assessments were conducted during the pre-treatment (baseline) phase and, in cases of non-pregnancy, three months post-treatment by a gynecologist. Findings: The results indicated that in all 10 cases, successful pregnancies occurred within a maximum of one year, leading to the birth of healthy infants. Conclusion: Based on the findings of this study, it can be concluded that Tajik lifestyle modification is effective in achieving successful pregnancies in women candidates for oocyte donation, even with an ovarian reserve below 0.2.